Akibat Diharamkannya Mengonsumsi Makanan dan Minuman yang Mengandung Alkohol dalam Islam Bagi Kesehatan Manusia - Siti bella; Sofi Nabila Doni; Suci Cantika Azhara; Alga Dwi Destoarezkya; Ahlun Nazi Siregar (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Food and drinks that contain alcohol are foods and drinks that are prohibited from consumption both in the Koran and health science. Formulation of the problem of the consequences of consuming food and drinks containing alcohol in Islam for human health. The aim of the research is to determine the consequences of consuming food and drinks containing alcohol in Islam for human health. The results of this research are that Islam prohibits consuming intoxicating foods and drinks. In Islam, food and drink are haram because they have very dangerous effects on humans. Apart from physical damage, alcohol can also damage a person’s soul. And this is very contrary to Islamic teachings which want to build strong people physically, mentally and spiritually.